1988
DOI: 10.1086/physzool.61.6.30156160
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Doubly Labeled Water Technique in Small Insectivorous Bats by Comparison with Indirect Calorimetry

Abstract: The doubly labeled water technique (DL W) tor the measurement of free-living energy expenditure was validated by comparison with indirect calorimetry for nine small « 1a g) insectivorous bats (n = 7. Pipistrellus pipistrellus: n = 2. Plecotus auri tus) over a fivefold range of daily metabolism. The DL W estimates were consistentlv greater than the indirect calorimetry estimates. The mean algebraic difference was +9.5% with the Lifson and :YtcClintock equation. +5.1 % with the Coward et al. equa tion. and-+-3..… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…A study on two small insectivorous bat species showed that a 5-fold range of average energy metabolism measurements could be generated using this method, when bats employed torpor to differing degrees (Speakman and Racey, 1988). Here, we show that regardless of torpor bout length there is a strong correlation between f H and V · O 2 across a complete torpor bout and at rest, consistent with the potential for the f H method to reliably measure field energy expenditure.…”
Section: Research Articlesupporting
confidence: 80%
“…A study on two small insectivorous bat species showed that a 5-fold range of average energy metabolism measurements could be generated using this method, when bats employed torpor to differing degrees (Speakman and Racey, 1988). Here, we show that regardless of torpor bout length there is a strong correlation between f H and V · O 2 across a complete torpor bout and at rest, consistent with the potential for the f H method to reliably measure field energy expenditure.…”
Section: Research Articlesupporting
confidence: 80%
“…In the calculations we assumed a fixed evaporation of 25% of the water flux (equation 7.17 [25]). Eighty-nine percent of final blood samples were obtained within three hours of a 24 h interval from the initial blood sample, which controlled for circadian rhythms of activity (max  =  7.2 h from 24 h interval [27], [28]). The average body mass of weasels, based on values obtained at the beginning and end of the DLW technique, was used in all analyses.…”
Section: Methodsmentioning
confidence: 99%
“…This method has been previously validated by comparison to indirect calorimetry in a range of small mammals (e.g. Speakman and Racey, 1988a) and provides an accurate measure of DEE over periods of several days (Speakman and Król, 2005b). Dayto-day variability in estimated energy metabolism suggests measurements spanning multiple 24·h periods may give a superior representation of energy metabolism (Speakman et al, 1994;Berteaux et al, 1996).…”
Section: Daily Energy Expenditurementioning
confidence: 99%